PENDIDIKAN HUKUM KRITIS PADA ANAK KONFLIK HUKUM (Studi Kasus di Rutan Kebon Waru Bandung) - Suparman, Asep (Jurnal Wawasan Yuridika, 2010)
Children in conflict with the Law residing at any state prison should have equivalent rights to education when compared to other children. A non formal way of teaching in forms of training and supervision could be provided in such a case. Law education is a part of coaching and guidance process which could be given to the children in conflict with the Law. Since law education at prisons is non formal in nature, the teaching of critical law education could as well be provided as an alternative in the process of coaching and guidance at the Calss 1 State Prison of the city of Bandung, Indonesia. According to the research, the author, findings as the result of the study are ; First, critical law education for children in conflict with Law is normatively based on the rules and regulations pertaining to training and supervision for prisoners and in mates. It is hoped that the children would gain a stronger personality and be more self determined; Second, the material to be given is applicable in nature, with emphasized on training and supervision to empower personality and self determination; Third, The method of education is dynamic, with a highlight on values through a process of guidance; Fourth, The process of education includes teaching of juridical and moral aspects of law, based on existing rules and regulations which highlight the level of requirements of the children, exploiting various sources close to their lives.The process of education is given separately in group or in blocks; Fifth, The process of critical law education has exercised every supporting aspect of education such as resources persons, messages, materials, tool, techniques/methods and physical and social environtment of the prison as the sources of education for the children while still consider their needs, availability, accessibility and cost consciousness in order for them to get hold of the said sorces.Keywords: Critical Legal Education - Relieve - ChildrensLegal Conflict